The Intelligent Search: Some Considerations on the Mon-tessori Method - Rossella Certini (Firenze University Press, 2013)
The author, on the assumption that «the Montessori "method" still today arouses much debate», reads some key points of her educational project. At the center of the reflection is, again, the scientific mind of the child, which is the key tool to learn how-experiment with the many dimensions of life. The Montessori method is still widely used in many parts of the world for its principles of democracy and active experience and the author explores some of the motivations behind these choices.